Use of genetically modified bacteria to repair cracks in concrete - Zhang, Zhigang (2020)
In this paper, we studied the crack-repair by spraying bacteria-based liquid around the cracks in concrete. To enhance the repair efficiency and speed up the repair process, the transposon mutagenesis method was employed to modify the genes of Bacillus halodurans and create a mutant bacterial strain with higher efficiency of calcium carbonate productivity by catalyzing the combination of carbonate and calcium ion. The efficiency of crack-repairing in concrete by spraying two kinds of bacterial liquid was evaluated via image analysis, X-ray computed tomography (X-CT) scanning technology and the sorptivity test. The results show that the crack-repair efficiency was enhanced very evidently by spraying genetically modified bacterial-liquid as no microbiologically induced calcite precipitation (MICP) was found within the cracks for concrete samples sprayed using wild type bacterial-liquid. In addition, the crack-repair process was also shortened significantly in the case of genetically modified bacteria.